The Impact of Prophetic Hadith on Enriching Rhetorical Studies - Al-Wadei, Asma Bint Ahmed Bin Misfer (Arts for Linguistic & Literary Studies, 2025)
This paper investigates the role of Prophetic Hadith in enriching Arabic rhetorical studies, emphasizing the interconnectedness between religious texts and linguistic sciences. It begins by establishing a foundational understanding of the concepts of influence and interdisciplinary exchange, particularly between Hadith studies and rhetoric. The research then explores the rhetorical perspective found in Prophetic critique, highlighting how Hadith commentators contributed not only to understanding rhetorical concepts but also to developing analytical methods for interpreting Prophetic discourse. The study sheds light on their efforts in assessing the rhetorical value of weak or fabricated Hadiths, often applying rhetorical principles in the evaluation process. Divided into three key sections, the paper discusses (1) rhetoric as measured by Prophetic critique, (2) rhetorical dimensions within Hadith compilations, and (3) the influence of Hadith authentication judgments on rhetorical standards. The findings reveal that Hadith scholars have provided valuable insights that significantly enrich Arabic rhetorical traditions. The study calls for a deeper integration of these contributions into modern rhetorical research, aiming to elevate the status of rhetoric within the broader spectrum of Islamic and linguistic sciences.